Vinylene carbonate: beyond the ethyne surrogate in rhodium-catalyzed annulation with amidines toward 4-methylquinazolines. Issue 32 (24th March 2021) - Wang, Chang; Fan, Xiaodong; Chen, Fan; Qian, Peng-Cheng; Cheng, Jiang
Abstract : Vinylene carbonate: acetylation reagent rather than ethyne surrogate in rhodium-catalyzed annulation with amidines toward 4-methylquinazolines. Abstract : In this paper, we developed a rhodium-catalyzed annulation of vinylene carbonate with amidines, leading to 4-methylquinazolines with moderate to excellent yields. This procedure proceeded by sequential ortho -acylation and annulation, where vinylene carbonate served as the acetylation reagent rather than the ethyne surrogate.